HUBUNGAN PAPARAN DEBU ASBES TERHADAP KAPASITAS VITAL PARU PADA PEKERJA PEMBUAT ASBES DI AREA FINISHING LINE PT. X JAWA TENGAH - Ferry Abidin; Ari Suwondo; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2015)
The Relation Of Asbestos Dust Exposure To The Pulmonary Vital Capacity Of On The Asbestos Makers At The Finishing Line Area In PT. X Central Java: The high level of dust in the workplace increased the risk of the respiratory disorder. Respiratory disorder could affect the impairment of someone’s pulmonary vital capacity. Asbestos sanding is one of causes that arises the asbestos dust at the workplace in PT. X Central Java. The purpose of this research was to find out the total dust level at the workplace and the characteristics of the workers (working period, smoking habit, ages, nutrition status, and exercising habit) which related to the pulmonary vital capacity on the asbestos makers at the Finishing Line area in PT. X Central Java.The method used in this research was observational approach with Study Cross Sectional design. The total sampel was 30 (thirty) workers with total techniques of sampling. This research was using the Chi Square and Fisher’s Exact tests to analyze the data. Based on the result of statistical test, it was known that there was any relation between the total dust levels and the pulmonary vital capacity (p=0,006) and it was true that dust indeed was a risk factor, there was no relation between the working period and the pulmonary vital capacity (p=0,399), there was no relation between the smoking habit and the pulmonary vital capacity (p=0,669), there was no relation between the age and the pulmonary vital capacity (p=0,071), there was no relation between the nutrition status and the pulmonary vital capacity (p=0,392), there was no relation between the exercising habit and the pulmonary vital capacity (p=1,000). The suggestions in this research were that the mask used by the workers should be replaced every day and there should be any local ventilation in the workplace.